Diagnostik Pengaruh bagi Model Risiko Bersaingan dengan Tapisan Sebagai Satu Risiko - Ibrahim, Noor Akma; Daud, Isa (1992)
Met-hods of detecting in fluential obseroations for competing risks model with censoring as one of the risk in a two-risks model are proposed. These methods include deletion of obseroations, one·step deletion, Cook distance and likelihood distance. Emphasis is on assessing the impact of an obseroation on the parameter estimation. Two sets of data are used to illusrate these techniques.